2001
DOI: 10.1063/1.1328043
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Does the structural superionic phase transition at 231 °C in CsH2PO4 really not exist?” [J. Chem. Phys. 110, 4847 (1999)]

Abstract: Superionic materials have intrigued researchers because they exhibit structural transitions from the paraelectric to the superionic phase which are accompanied by an increase of the electrical conductivity as much as five orders of magnitude. Notwithstanding the number of studies and variety of experiments that have been carried out on superprotonic crystals of the KH 2 PO 4 type, no generally agreed-upon model describing the structural and chemical features that induce superionic transitions exists. Discrepan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 14 publications
2
53
0
Order By: Relevance
“…With the powder X-ray diffraction (XRD) measurement of CDP in the H 2 O-saturated atmosphere, it has been reported that a structural transformation occurs at ca. 231°C from the monoclinic phase (P2 1 /m) to the cubic phase (Pm-3m) without any decomposition [8]. Thus, the previous studies show that CDP high-conducting phase is stable in appropriate humidity.…”
Section: Introductionmentioning
confidence: 76%
“…With the powder X-ray diffraction (XRD) measurement of CDP in the H 2 O-saturated atmosphere, it has been reported that a structural transformation occurs at ca. 231°C from the monoclinic phase (P2 1 /m) to the cubic phase (Pm-3m) without any decomposition [8]. Thus, the previous studies show that CDP high-conducting phase is stable in appropriate humidity.…”
Section: Introductionmentioning
confidence: 76%
“…228 uC. [1][2][3][4] The superprotonic phase of CsH 2 PO 4 exhibits proton conductivity greater than 10 22 S cm…”
Section: Introductionmentioning
confidence: 99%
“…Following Lee [3] Ortiz et al [4] and recently Park et al [5] attribute the increase in conductivity at high temperature region of CDP (as well as in other KDP-family compounds) to dehydration process starting on the sample surfaces and partial polymerization. On the other hand our previous powder X-ray investigations of CDP under humidified conditions [6,7] support Baranov's et al [1] suggestion, that superprotonic phase of CDP is cubic and reversible with hysteresis on cooling. Recently Boysen et al [8] and Otomo et al [9] reconfirmed the reversibility of the superionic phase transition in these crystals.…”
mentioning
confidence: 73%